Investigating the affordability of housing ownership among millennials in Penang / Nurfarisha Amira Ahmad Subri - Ahmad Subri, Nurfarisha Amira (2023)
Homeownership is recognized as a fundamental human need, but it remains a significant challenge in many developing countries, including Malaysia. This study addresses the persistent concern of affordable housing in Malaysia, specifically focusing on the challenges faced by Millennials in Penang. Rising house prices and low incomes hinder their ability to purchase homes, highlighting the need for targeted research and guidance. The lack of specific discussions on housing affordability in Penang for Millennials and the impact of demographic factors further emphasize the significance of this study. The aim of this research is to identify factors that influencing housing affordability among Millennials that benefit prospective buyers, developers, policy makers, and local authorities and rank the significant factors in influencing Millennials homeownership affordability. The study's scope encompasses Penang as a severely unaffordable housing market, targeting Millennials aged 20-40 years old. Questionnaire survey has been used to collect the data from the respondents. The total respondents that response to the survey are 400 respondents. However, the researcher had sort out the inappropriate respondents and only 384 valid samples are collected from the total of 400 samples distributed. The data collection employed a quantitative survey method, and the analysis utilized descriptive analysis of frequency analysis, mean analysis, and the Relative Important Index (RII).